The epidemiology of avian pox and interaction with avian malaria in Hawaiian forest birds. Issue 4 (6th June 2018) - Samuel, Michael D.; Woodworth, Bethany L.; Atkinson, Carter T.; Hart, Patrick J.; LaPointe, Dennis A.
Abstract: Despite the purported role of avian pox ( Avipoxvirus spp.) in the decline of endemic Hawaiian birds, few studies have been conducted on the dynamics of this disease, its impact on free‐living avian populations, or its interactions with avian malaria ( Plasmodium relictum ). We conducted four longitudinal studies of 3–7 yr in length and used generalized linear models to evaluate cross‐sectional prevalence of active pox infection and individuals with healed deformities that had recovered from pox. Our goal was to understand how species, season, elevation, malaria infection, and other biological characteristics influenced pox infection in ʻApapane, Hawaiʻi ʻAmakihi, ʻIʻiwi, and Japanese White‐eye across low‐, mid‐, and high‐elevation forests on the island of Hawaiʻi. We also used multi‐state capture‐recapture (longitudinal) models to estimate pox infection rates, recovery rates, and potential pox‐related mortality. Pox infection rates were typically highest in low‐elevation forests, followed by mid‐elevation forests, and lowest in high‐elevation forests. We also found seasonal changes in pox prevalence throughout the annual cycle; typically increasing from spring through summer, peaking in fall, and declining in winter. These seasonal changes occurred in low‐ and mid‐elevation forests, but not in high elevations where pox infection was low. Seasonal and elevation patterns of pox infection are like those for avian malaria, strongly implicating mosquito vectors, rather than other biting arthropods or contact transmission, as the primary source of transmitting both diseases. Most native Hawaiian birds recovered from pox infection within 6 months; frequently without permanent lesions. Contrary to our expectations, we found no direct evidence that pox is a substantial mortality factor in any of the three native bird species we studied. Birds with chronic malaria infection were more likely to have both active pox infection and healed pox lesions suggesting a synergistic interaction that may influence the evolution of pox virulence. Because pox infection can be assessed visually, and birds have a high recovery rate, this disease may be a sensitive indicator of the seasonal and annual risk of transmission of malaria in Hawaiʻi.